Engagement des communautés face au changement climatique : une expérience de gestion intégrée à Le Goulet et Pointe-du-Chêne au Nouveau-Brunswick - Omer Chouinard; Steve Plante; Gilles Martin (VertigO)
Le Goulet and Pointe-du-Chêne are two New Brunswick coastal communities facing serious flooding and coastal erosion problems. These two communities are different on cultural, economical and social point of view. Since 2003, researchers from Université de Moncton have been engaged in a participatory action research with representative local people of different coastal communities. Also they have invited the decision makers and civil servant of the province of New Brunswick and Environment Canada to involve the communities in a decision making process focussing on adaptation and proactive measures to these major problems. The community engagement process involves an inventory of local perceptions, knowledge, adaptation measures already tried, preoccupations, awareness, information building and decision making through focus group techniques. Semi-directed interviews were held prior to and at the end of the data gathering process. Results show participants used some adaptation techniques although they lack resources and direction. The engagement process resulted in an important change in adaptation approaches envisioned for the future in the village of Le Goulet and brought forward some new solutions in the two communities. Participants viewed the process as leading to more sustainable solutions for their communities or as a means to provide more credibility to proposed solutions before seeking government resources. To encourage a broader participation, researchers need to better identify objectives and possible outcomes from the start of the process to have a better participatory action research.